1998
DOI: 10.1080/08913819808443480
|View full text |Cite
|
Sign up to set email alerts
|

Man, society, and the failure of politics

Abstract: The activity of the hippocampus is modulated by a serotonergic projection from the midbrain. Corticosteroids regulate the activity of this raphe-hippocampal system in various ways. These effects are differentially mediated via two types of central corticosteroid receptor types, the high-affinity mineralocorticoid receptor (MR), and the lower affinity glucocorticoid receptor (GR). Under physiological fluctuations of corticosteroid concentrations, predominantly MR-mediated effects suppress the activity of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…At lower corticosterone levels MR activation alone downregulates 5-HT1A receptors and suppresses of serotonin-related activity in the raphe-hippocampal system. Transient increases in glucocorticoid concentrations producing GR occupation rapidly increases the ability for hippocampal neurons to respond to 5-HT1A receptor stimulation, attenuates 5-HT autoinhibition, and facilitates stress-induced increases in 5-HT release, in part by increasing calcium influx and depolarizing the neurons (234,298). These concentrations also bind MR which through transrepression of the 5-HT1A receptor promoter by the MR:GR heterodimer, restores normal 5-HT1A receptor signaling after an appropriate delay and allows the brain to adapt to stress (343).…”
Section: Pathophysiological Implications Of Inappropriate Mr Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower corticosterone levels MR activation alone downregulates 5-HT1A receptors and suppresses of serotonin-related activity in the raphe-hippocampal system. Transient increases in glucocorticoid concentrations producing GR occupation rapidly increases the ability for hippocampal neurons to respond to 5-HT1A receptor stimulation, attenuates 5-HT autoinhibition, and facilitates stress-induced increases in 5-HT release, in part by increasing calcium influx and depolarizing the neurons (234,298). These concentrations also bind MR which through transrepression of the 5-HT1A receptor promoter by the MR:GR heterodimer, restores normal 5-HT1A receptor signaling after an appropriate delay and allows the brain to adapt to stress (343).…”
Section: Pathophysiological Implications Of Inappropriate Mr Activationmentioning
confidence: 99%
“…These concentrations also bind MR which through transrepression of the 5-HT1A receptor promoter by the MR:GR heterodimer, restores normal 5-HT1A receptor signaling after an appropriate delay and allows the brain to adapt to stress (343). However, chronic stress leads to chronic heterodimer formation and repression of 5-HT1A receptor transcription and depression-related behavior that led to the development of the selective serotonin reuptake inhibitors in use today (242, 298). As described in the section on epigenetic modifications of the MR and GR, chronic stress produces in rats many of the same biochemical changes found in depression (426).…”
Section: Pathophysiological Implications Of Inappropriate Mr Activationmentioning
confidence: 99%
“…When circulating levels of corticosterone are the lowest (early morning in nocturnal species like mice), 70–95% of MR are occupied, whereas GR are activated mainly by higher circulating levels of corticosterone (in the evening or during stress). Although the effects of ADX are usually explained by the suppression of the tonic effects of MR, some of the previously cited effects observed after ADX were reversed by the GR agonist dexamethasone but not by the MR agonist aldosterone [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Although some authors reported no change in indices of the basal metabolism of serotonin (5-hydroxytryptamine, 5-HT) in the hippocampus, cortex or striatum after adrenalectomy (ADX) [1, 2], others, using different recovery periods after surgery, showed that removal of corticosterone reduces indices of basal 5-HT synthesis and turnover in the brain stem where the raphe nuclei which contain the serotoninergic cell bodies are located and also in the hippocampus and hypothalamus [3, 4, 5]. Moreover, many studies reported that basal circulating corticosterone levels exert inhibitory effects on mRNA expression and/or binding characteristics and functions of 5-HT 1A , 5-HT 1B and 5-HT 2C receptors, particularly in the hippocampus, and some of these effects could be the consequence of corticosterone-induced changes in 5-HT turnover [6, 7]. The effects of corticosterone are mediated by two types of receptors: the mineralocorticoid receptors (MR) and the glucocorticoid receptors (GR) which bind corticosterone with a 5- to 10-fold lower affinity than MR.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the balance of mineralocorticoid/glucocorticoid receptor activation can be altered by chronic changes of corticosteroid concentrations in combination with glucocorticoid feedback resistance. Such an imbalance would lead to a relative dominance of mineralocorticoid-receptor-mediated suppressive effects on the activity of the raphe-hippocampal system, which may be a biologically relevant aspect of depression [5]. However, the data regarding corticosteroid control of 5-HT receptors, other than 5-HT 1A , are scarce and contradictory.…”
Section: Introductionmentioning
confidence: 99%